The Health Economic Impact of Musculoskeletal Physiotherapy Delivered by Telehealth: A Systematic Review - Darryn Marks; Sarah Kitcher; Elodie Attrazic; Wayne Hing; Michelle Cottrell (International Journal of Telerehabilitation)
Introduction: While the efficacy of telehealth in musculoskeletal physiotherapy has been supported, its cost effectiveness has not been established. Therefore, the objective of this review was to ascertain the health economic impact of outpatient musculoskeletal physiotherapy delivered by telehealth and describe methodology utilized to date. Methods: Electronic searching of PubMed, CINHAL, PEDro, and Web of Science databases was undertaken alongside handsearching for publications comprising: population: adults with musculoskeletal disorders managed in any type of outpatient ambulatory setting; intervention: physiotherapy delivered by telehealth comparison: traditional in-person physiotherapy; and, outcomes: economic analyses reporting costs and consequences. Appraisal was undertaken with the Downs and Black Questionnaire and the Consolidated Health Economic Evaluation Reporting Standards Checklist. Results: Eleven studies of mixed methodological quality were included. Most were conducted in the public sector, from the economic perspective of the health service funder. Telehealth consistently produced health outcomes akin to in-person care. In all but one, telehealth was less costly, with savings achieved by reducing in-person consultations and travel costs. Conclusion: Telehealth is as effective and cheaper than in-person physiotherapy for musculoskeletal disorders in public hospital outpatients. Further health economic research is needed to clarify the economic impact of telehealth upon non-government providers of musculoskeletal physiotherapy.